2017
DOI: 10.1186/s12905-017-0436-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep quality and cardiovascular disease risk in Chinese post-menopausal women

Abstract: BackgroundMenopause is an inevitable stage affecting every middle-aged woman. China has a large and increasing group of post-menopausal women. Most post-menopausal women suffer from increased risks for cardiovascular diseases (CVD) and sleep problems. Previous studies have demonstrated the associations between sleep disorders and increased CVD risks in general population. The current study is to examine the relationship between sleep quality and CVD risks among Chinese post-menopausal women.MethodsThis study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…81 In summary, primary sleep disorders become more prevalent in older age, affecting > 53% of postmenopausal women. [103][104][105] Moreover, poor sleep in perimenopausal/postmenopausal women is associated with inflammation, 106 cardiovascular and metabolic disease, [107][108][109] and mood disorders. Understanding the evolution of sleep across a woman's life span may lead to effective therapies that affect women's health and quality of life.…”
Section: Sleep Changes Related To Mood Disordersmentioning
confidence: 99%
“…81 In summary, primary sleep disorders become more prevalent in older age, affecting > 53% of postmenopausal women. [103][104][105] Moreover, poor sleep in perimenopausal/postmenopausal women is associated with inflammation, 106 cardiovascular and metabolic disease, [107][108][109] and mood disorders. Understanding the evolution of sleep across a woman's life span may lead to effective therapies that affect women's health and quality of life.…”
Section: Sleep Changes Related To Mood Disordersmentioning
confidence: 99%
“…The higher prevalence of obstructive sleep apnea in adults with obesity is one of the possible causes of impaired sleep quality [8]. Low sleep quality was associated with lower QoL, more depressive symptoms and an increased cardiovascular disease risk [911]. These interrelations underline the importance of helping individuals not only with their obesity but also their associated mental health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…As lifestyle-related factors such as stress [10], smoking [11], caffeine [12], and sleeping quality [13] can produce cardiovascular changes, the present study considered them and revealed no statistically significant. Although the random distribution of these factors was relatively similar amongst both groups (committed and uncommitted), there were no apparent variations.…”
Section: Discussion:-mentioning
confidence: 73%